Representation of Pollution in Media: A Critical Discourse Analysis of Newspapers’ Headlines - Ahmad, Ali; Hafeez, Muhammad Rashid; Sajid, Muhammad Akbar (International Journal of Psychosocial Rehabilitation, 2020)
This paper critically decodes the newspapers’ post titles to highlight how same event is represented differently by print media through their headlines. The present study attempts to locate how discursive techniques are employed differently by different newspapers to propagate desired ideologies to the target readership regarding the representation of smog phenomenon. In this regard four Pakistani English Daily (The Dawn, The News International, Pakistan Today, The Express Tribune) and four Indian English Daily (Hindustan Times, The Hindu, The Times of India, The Indian Express) have randomly been selected to show how Environmental changes are discursively represented by different ideological groups. The news on the selected issue published in 2017 and 2018 have been randomly selected for analysis. The present research employs Van Dijk’s (2004) Socio Cognitive model to critically analyze the use of different linguistics moves to represent an event accordingly. It suggests that language is one of the best sites to invest ideology and to shape the mindset of the target audience. This research model has been made operational through inclusion and exclusion process. Some of the analytical categories, missing in the existing data have been excluded. The findings of the research suggest how print media discourses are used as an insidious weapon to represent same event differently. This is how the concept of linguistic solidarity and distance is played up. The post titles of print media propagate different worldviews by camouflaging one thing at the cost of other.